Sosialisasi Dan Pelatihan Pemasaran Online Berbasis Digital Untuk Meningkatkan Omset Penjualan UMKM Desa Pageraji - Sumantri, R Bagus Bambang; Triwibowo, Deny Nugroho; Ariyanto, Arif Setia Sandi; Jayusman, Hadi (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
Digital transformation brings significant changes in marketing strategies, especially for Micro, Small, and Medium Enterprises (MSMEs) in Pageraji Village. Increased internet accessibility has opened up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in Pageraji Village to expand their reach and increase their sales turnover. This journal documents the socialization and training of digital-based online marketing to help MSMEs in Pageraji Village utilize digital potential. The socialization begins with an in-depth understanding of the benefits of online marketing and its positive impacts on the development of MSMEs. The training focuses on key aspects, optimizing social media and marketplaces, and data analysis for smarter decision making. The results of the socialization and training show an increase in participants' understanding and skills in implementing online marketing strategies. Participants were able to increase their digital presence, reach new market share, and significantly increase their sales turnover. This journal reflects the importance of an inclusive approach in supporting MSMEs at the village level to adapt to digital change. This study contributes to a practical and contextual understanding of how online marketing can be a catalyst for local economic growth in the digital era.